Ab Initio energetics of SiO bond cleavage. Issue 27 (27th July 2017) - Hühn, Carolin; Erlebach, Andreas; Mey, Dorothea; Wondraczek, Lothar; Sierka, Marek
Abstract : A multilevel approach that combines high‐level ab initio quantum chemical methods applied to a molecular model of a single, strain‐free SiOSi bridge has been used to derive accurate energetics for SiO bond cleavage. The calculated SiO bond dissociation energy and the activation energy for water‐assisted SiO bond cleavage of 624 and 163 kJ mol −1, respectively, are in excellent agreement with values derived recently from experimental data. In addition, the activation energy for H2 O‐assisted SiO bond cleavage is found virtually independent of the amount of water molecules in the vicinity of the reaction site. The estimated reaction energy for this process including zero‐point vibrational contribution is in the range of −5 to 19 kJ mol −1 . © 2017 Wiley Periodicals, Inc. Abstract : A multilevel approach that combines high‐level ab initio quantum chemical methods has been used to derive accurate energetics for SiO bond cleavage. The calculated SiO bond dissociation energy and the activation energy for water‐assisted SiO bond cleavage of 624 and 163 kJ mol −1, respectively, are in excellent agreement with values derived recently from experimental data.